A comparison of methods to determine equine laterality - Kuhnke, S.; König von Borstel, U. (DCA Report; Nr. 044, 2014)
The study aimed at comparing agreement between results obtained by different methods to determine equine laterality. Three groups of warm-blood horses (n=67, age 0.25-23 years) were classified according to their preferred advanced foreleg during grazing (scan sampling at 30 or 60 second intervals for 2 hours), lateral displacement of their hindquarters in relation to the median plane, visual laterality and preferred side specified by their riders. Cross-tabulations of two characteristics with 2-5 values were investigated for random distribution using chi-square tests, phi and Cramer's-V in SPSS. In a 30 second scan sampling 11 horses tended towards leg preference (z-value >±1). Significant (z-value >±1.96) leg preference was detected in 6 horses. Results changed considerably with the 60 second sampling: leg preference and associated significance levels remained, increased or decreased between both samples but never changed direction (P<0.001). The majority of horses were not ridden. Most ridden horses with their hindquarters displaced to the right (n=14) were classified as right-lateralised by their riders. Some, however, were described as left-lateralised. Riders classified all horses with their hindquarters displaced to the left (n=7) as left-lateralised (P=0.003). Right-lateralised horses did not show a significant leg preference. Some, however, tended to prefer their left (14.3%) or right leg (7.1%). Left-lateralised horses tended to or significantly preferred their left leg (28.6%) or showed no preference (71.2%) (60 second interval, P=0.018). During frontal approach with objects (plastic bag, toy, ball), most horses did not prefer any eye (80-88%). Except for one horse, only left sensory bias was detected. Left-eye preference was observed only in horses with a left-leg or no preference (P=0.005/0.009). The preferred left foreleg during grazing seems to correlate with preference of the left eye and left side during riding. However, this does not apply to horses preferring the right leg. The displacement of the hindquarters correlates with laterality during riding in all left, but not all right-lateralised horses. Motor bias during grazing seems to be accurate according to the direction, but not the degree or actual occurrence. Thus, the agreement between different aspects of laterality in horses seems to be limited to specific measures and outcomes. Attention should be paid to the desired information when selecting methods for assessment of laterality. LP: Laterality in horses can be more accurately determined in left-lateralised horses. The displacement of the hindquarters indicates the preferred side during riding for left-, but not all right-lateralised horses. Leg preference during grazing, if shown, can indicate the preferred side.